Physiological strength of lipoic acid in copper intoxication - J. Jovanovic Mirkovic; G. Kocic; C. Alexopoulos; Z. Jurinjak (European Psychiatry, 2022)
Introduction The average concentration of copper in the air, e.g. in the USA it ranges from 5–20 ng/m3, in soil from 5–70 mg/kg, and the intake of copper from food is 1.0–1.3 mg/days for adults (0.014–0.019 mg/kg/day) (Barceloux, 1999). The effect of lipoic acid is reflected in the intensification of ATP synthesis, participates in the assimilation of lactic acid, activates the enzyme cycle of tricarboxylic acid, stimulates the growth of lactic acid bacteria by replacing acetate (acetate transfer factor), stimulates CoA synthesis (fatty acid utilization), prevents liver damage by various toxins, normalizes aldolase and transferase levels.